Evaluation of E-Government Effectiveness in Tehran Water and Wastewater Company - HOSSEINI, SEYED MOJTABA; ESLAMBULCHI, ALIREZA; MANDEJIN, MOHAMMAD REZA RABIEE; SAREM, ALI ASGHARI (The journal of contemporary issues in business and government, 2020)
In line with the development of e-government, Tehran Water and Wastewater Company can examine its current status from various aspects of ICT development and improve their desirability by planning on relevant indicators and criteria. In this regard, the purpose of this study was to evaluate the effectiveness of e-government development. Statistical population in the qualitative part was the managers and in the quantitative part of the research it consists of a number of managers in the field of information technology of Tehran Water and Wastewater Company with 13 subsidiaries comprising 240 persons. The sample size was determined by Cochran formula and simple random stratified method. 148 individuals were selected as sample size. In order to collect data in the qualitative part, an open questionnaire was used and in the quantitative part a closed questionnaire was used. Expert opinion was used to determine the validity of the questionnaire and Cronbach's alpha was used to determine the reliability, and the results showed that the reliability was confirmed. Structural equations with AMOS software were used for data analysis. The results showed that the model has 7 dimensions which include structural, behavioral, environmental, process factors, output, outcome and impact that can be effective in applying e-government in Tehran Water and Wastewater Company, also the necessary investigations for fitness of the results showed that the proposed model has a good fit. Therefore, this model can be used to evaluate the effectiveness of e-government application in Water and Wastewater Company.